2002
DOI: 10.1038/416832a
|View full text |Cite
|
Sign up to set email alerts
|

Rapid freshening of the deep North Atlantic Ocean over the past four decades

Abstract: The overflow and descent of cold, dense water from the sills of the Denmark Strait and the Faroe Shetland channel into the North Atlantic Ocean is the principal means of ventilating the deep oceans, and is therefore a key element of the global thermohaline circulation. Most computer simulations of the ocean system in a climate with increasing atmospheric greenhouse-gas concentrations predict a weakening thermohaline circulation in the North Atlantic as the subpolar seas become fresher and warmer, and it is ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
400
2
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 504 publications
(423 citation statements)
references
References 20 publications
18
400
2
3
Order By: Relevance
“…Although solar-forcing cannot be ruled out as a triggering mechanism, the SST variability discussed above was not synchronous across the North Atlantic for the MCA-LIA interval. In fact, west-to-east "provincialism" in North Atlantic climate has been observed over several timescales: in Holocene millennial-scale sea-ice and surface salinity (de Vernal and Hillaire-Marcel, 2006) and SST in the North Atlantic (Keigwin and Pickart, 1999;deMenocal et al, 2000), 20th century decadal sea-ice fluctuations (Deser et al, 2000), and SST and deep water formation during the last few decades (Dickson et al, 2002). The temperature patterns presented above thus support paleoceanographic evidence (Newton et al, 2006) and model simulations (Renssen et al, , 2007Saenger et al, 2009) that suggest coupled oceanic-atmospheric processes, possibly involving deep-water formation in subpolar regions, may have influenced regional climate during the MCA-LIA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although solar-forcing cannot be ruled out as a triggering mechanism, the SST variability discussed above was not synchronous across the North Atlantic for the MCA-LIA interval. In fact, west-to-east "provincialism" in North Atlantic climate has been observed over several timescales: in Holocene millennial-scale sea-ice and surface salinity (de Vernal and Hillaire-Marcel, 2006) and SST in the North Atlantic (Keigwin and Pickart, 1999;deMenocal et al, 2000), 20th century decadal sea-ice fluctuations (Deser et al, 2000), and SST and deep water formation during the last few decades (Dickson et al, 2002). The temperature patterns presented above thus support paleoceanographic evidence (Newton et al, 2006) and model simulations (Renssen et al, , 2007Saenger et al, 2009) that suggest coupled oceanic-atmospheric processes, possibly involving deep-water formation in subpolar regions, may have influenced regional climate during the MCA-LIA.…”
Section: Discussionmentioning
confidence: 99%
“…The Labrador Current (LC), a branch of Labrador Sea Water formed near the shelf/slope break off maritime Canada, is an important distal source of MAB-Chesapeake Bay water. On decadal timescales, the strength of the LC is linked to i) North Atlantic Oscillation (NAO) decadal climate variability, ii) the Atlantic Meridional Overturning Circulation (AMOC) including Labrador Sea deep-water formation, and iii) wind-driven processes in the North Atlantic (e.g., Dickson et al, 2002). Thus, bay temperature variability should reflect that of its source water in the MAB, and more broadly, ocean-atmosphere Karlsen et al (2000), Cronin et al (2000), Zimmerman and Canuel (2002).…”
Section: Regional Oceanographymentioning
confidence: 99%
See 1 more Smart Citation
“…As the North Atlantic is one of the few regions of the world ocean where deep waters are formed, this freshwater signal is being transferred into the deep oceans [Dickson et al, 2002]. Additionally, as a major source of deep waters for the world ocean and thus, a key player in the global meridional overturning circulation, the high latitude North Atlantic is potentially very sensitive to additions of freshwater (through freshwater's role as a stabilizing element in the buoyancy budget).…”
Section: Introductionmentioning
confidence: 99%
“…[2] A number of recent studies [Dickson et al, 2002;Curry et al, 2003] have suggested that the high latitudes of the North Atlantic Ocean have been freshening over the last several decades. As the North Atlantic is one of the few regions of the world ocean where deep waters are formed, this freshwater signal is being transferred into the deep oceans [Dickson et al, 2002].…”
Section: Introductionmentioning
confidence: 99%